EFEKTIFITAS PENGGUNAAN MEDIA EDUKASI BUKU SAKU DAN LEAFLET TERHADAP PENGETAHUAN DAN KEPATUHAN DIET PASIEN RAWAT JALAN DIABETES MELITUS TIPE 2 DI PUSKESMAS - Muniratul Hidayah; Sopiyandi Sopiyandi (Pontianak Nutrition Journal (PNJ), 2018)
Educational activities is one strategy to the management of diabetes mellitus. Education is the activity of delivering health messages to groups or individuals in order to gain a better knowledge. The selected media is pocket books and leaflets, booklets chosen because it is simple, brief, and contains a lot of information. The purpose of this study to determine the effectiveness of the use of educational media pocket books and leaflets on knowledge and dietary compliance of outpatients with diabetes mellitus type 2 in the clinic. The research is a Quasi-Experiment with design used is Pretest-Posttest designnamely in the two groups conducted a pretest to determine the initial state before being given a different treatment, and both were also given the posttestusing the Wilcoxon test and Mann-Whitney test with a significance level of = 0.05. The results showed no significant differences in knowledge after being given nutrition education with media pocket books and leaflets p value. knowledge of 0,000 (Sig. <0.05), whereas the p valuesÂ  Â obtained compliance. amounted to 0,641 (p. <0.05) showed no significant difference in adherence respondents after being given nutrition education with media pocket books and leaflets. It is concluded that there are differences in knowledge after being given nutrition education with media pocket books and leaflets. However there was no difference in compliance after being given nutrition education with media pocket books and leaflets.